LOCAL RICE RESPONSE TO MENTIK POWDER TECHNOLOGY APPROACH SRI (SYSTEM OF RICE INTENSIFICATION) AND INTEGRATED CROP MANAGEMENT - Kristamtini Kristamtini; Setyorini Widyayanti; Siti Rahayu (Pusbindiklat - LIPI, 2011)
Mentik wangi is one of the local rice varieties that need to be conserv and explored its potential. Therefore, research is needed that aims to determine the response of local rice fragrant mentik technology approach System of Rice Intensifi cation (SRI) and Integrated Crop Management (ICM). SRI goals and ICM on the same principle is to increase farmers’ production with different targets and different managers. Research conducted in Jayan Village, Kebon Agung, Imogiri in May 2009 (MK 2009). Research carried out on land owned by farmers with a total area of 2000 m2. Planted rice varieties are fragrant with mentik treatment 2 repeated 3 times. The fi rst treatment is the SRI technology approaches, including: age of young seedlings (14 the day after the scatterplot), spacing of 30 x 30 cm,10 tons/ha of organic fertilizer, without the use of chemical pesticides. The second treatment is the approach of Integrated Crop Management (PTT), including: age of young seedlings (14 the day after the scatterplot), spacing of 25 x 25 cm, 2 tons/hectar of organic fertilizer, 250 kg/ha Urea, 50 kg/ha Sp-36 and 50 kg/ha KCL). The results showed that the results achieved mentik fragrant rice with higher SRI approach (10.89 tons/hectar)compared with ICM technology, technological approach (9.22 tons/ha). Mentik wangi rice produced by SRI and the technology approach is pulen with ICM (SRI amilosa content = 15.65% and ICM = 15.96%), while levels of macro and micro elements mentik fragrant rice produced with higher ICM approach (Phosphor = 15.95 ppm; Fe = 2.48 ppm; Zn = 0.961 ppm; Cu = 0.426 ppm and Mg = 0.670 ppm) compared with the SRI approach (Phosphor = 15.13 ppm; Fe = 2.35 ppm; Zn = 0.648 ppm; Cu = 0.371 ppm and Mg = 0.623 ppm)